Kualitas Pengetahuan tentang Penggunaan Kosmetik dikalangan Masyarakat Melalui Virtual Referensi - Rusdiaman Rusdiaman; A. Rufaidah Hashary; Ayu Eka Putri (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
Cosmetics is unique product because in additionto having the basic needs of women for beauty. The purpose of study is to determine the quality of public knowledge of whitening cosmetics virtually. This study uses a literature study where the technique of collecting library data from several existing journals uses secondery data, then the data obtained is analyzed and concludedby means of texlar tabulation so as to obtained indicate that there is still a lack of public knowledge about the use of cosmetics.